2015
DOI: 10.1099/jmm.0.000176
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and microbiological outcomes in patients with Streptococcus anginosus group bacteraemia identified through use of a rapid microarray assay

Abstract: Limited data exist evaluating outcomes in patients with serious Streptococcus anginosus group infections, particularly bacteraemia. A retrospective, single-centre cohort study was conducted to characterize potential risk factors along with clinical and microbiological outcomes in patients with S. anginosus group bacteraemia (SAGB). Adult inpatients with SAGB identified using the Verigene Gram-positive blood culture assay between March 2013 and April 2014 were included. Patients aged j18 or .89 years, those wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…There is no gold standard for the identification of SAG. Cultivation methods and the available biochemical test are not sufficient for precise identification of the species, therefore it is necessary to use molecular techniques ( Wenzler et al, 2015 ; Kragha, 2016 ). Among them, two 16S rRNA real-time PCR assays were developed.…”
Section: Identification Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no gold standard for the identification of SAG. Cultivation methods and the available biochemical test are not sufficient for precise identification of the species, therefore it is necessary to use molecular techniques ( Wenzler et al, 2015 ; Kragha, 2016 ). Among them, two 16S rRNA real-time PCR assays were developed.…”
Section: Identification Methodsmentioning
confidence: 99%
“…The authors revealed that the source of S. anginosus group infections is usually the gastrointestinal tract (GI). The study by Wenzler et al (2015) found 18 cases (53% of 34 patients) with a gastrointestinal source of bacteremia; therefore, sepsis could have originated from an unidentified source of the GI tract. Siegman-Igra et al (2012) reported 215 cases of SAG infections, the most common sources being the liver and other intraabdominal abscesses.…”
Section: The Risk Factors For Streptococcus Anginosus ...mentioning
confidence: 99%
“…Chatelain et al corroborated these findings and also noticed a high number of radical reconstructive procedures (2/3) [ 4 ]. Regarding antibiotic choice, S. anginosus is almost always susceptible to penicillin and in most published literature beta-lactam antibiotics are the treatment of choice for SAG infections [ 7 , 15 ]. The adequate duration of antibiotic treatment has not been established yet.…”
Section: Discussionmentioning
confidence: 99%
“…Other additional circumstances that support the hematogenous spread of the infection are the patients' comorbidities. Hematogenous i n f e c t i o n s a r e p r e d o m i n a n t l y e n c o u n t e r e d i n immunocompromised and diabetics [9], and S. anginosus infections are mostly found in male adults with a history of cirrhosis, neoplasia, diabetes mellitus, and smoking [7,14,15]. The treatment of osteomyelitis consists of antibiotics, adequate surgical debridement, and bone fixation [2,9].…”
mentioning
confidence: 99%
“…Further, iNOS upregulation has been detected in cancer tissues (Doi et al, 1999;Marrogi et al, 2000;Zhang et al, 1998) and could be a risk factor for carcinogenesis (Ambs et al, 1999;Giardiello et al, 1993;Iwasaki et al, 1997;Jadeski and Lala, 1999). Because the environments of these organs are generally mild acidic conditions (Fallingborg, 1999;Hassen et al, 2015;Khutoryanskiy, 2015;O'Hanlon et al, 2013), the aciduricity of S. anginosus can be a pathogenicity trait, allowing the microorganism to promote infection in an acidic condition followed by an aberrant infection at other body sites, or systemic infections (Mak et al, 2011;Shah et al, 2017;Wenzler et al, 2015).…”
Section: Introductionmentioning
confidence: 99%